IMPLEMENTASI BANTUAN SOSIAL DALAM MENANGGULANGI KEBUTUHAN DASAR MASYARAKAT DI DESA MEKARSARI: Implementation Of Social Assistance In Addressing Basic Community Needs In Mekarsari Village - Aminullah, Aminullah; Jaya, Nenet Natasudian; Subrata, I Gusti Made; Marini, Ida Ayu Ketut; Apriani, Titin; Ardika, Gede Tusan; Titawati, Titin; ., Ramli; Loilewen, Aline Febriany (Yayasan Al-Amin Qalbu, 2024)
The aim of implementing community service in the form of social assistance is to temporarily address the basic needs of economically disadvantaged communities in Mekarsari Village. Methods for implementing service include: forming a service team, preparing service needs, collecting data on underprivileged communities, gathering the community and handing over aid. Service activities carried out include: 1) Formation of a service team consisting of lecturers, students, community and village government. 2) Preparation of the needs for implementing community service, 3) community data collection in collaboration with the village government, and 4) delivery of assistance in one place, so that the community can be given direction regarding the assistance received. The social assistance provided was 25 packages containing basic necessities or basic community needs. Assistance can only reduce people's expenses for 3 to 5 days, but people seem enthusiastic and grateful